Padrões de crescimento na infância e ocorrência de menarca antes dos 12 anos de idade : estudo de coorte de nascimento de Pelotas, 1982. - Mesa, Jeovany Martinez (2006)
Background: there is evidence that rapid growth in early childhood produces negative effects on health in later periods. However, the relationship between these early factors and puberty, especially with regard to the onset of menarche, has been poorly studied. Methods: the current study included 2083 women belonging to The 1982 Pelotas Birth-Cohort Study. Statistical analyses employed Pearson X2 and X2 for linear trends.Moreover, multivariate analyses were performed using Poisson regression, following a hierarquical model reflecting a life-course approach. Results: the mean of age of menarche was 12.4 years and the prevalence of menarche before age 12 was 24.3%. Increasing Z-score values for weight/age, height/age and weight/height at 19.4 and 43.1 months corresponded to linear tendencies of increasing prevalence and relative risks for the onset of menarche before age 12. The relative risks were systematically higher at 43.1 months than at 19.4 months. In addition, those girls who experienced rapid growth (gaining 0.67 Z-score or more) between birth and 19.4 months for weight/age Z-score or between 19.4 and 43.1 months for weight/age or height/age Z-score also showed greater risk. The risk of menarche before age 12 was highest when rapid growth in weight/age Z-score occurred in both periods and showed the highest value among girls who experience it and belonged to the first Williams curves tertile at birth. Rapid growth in weight/height Zscore was not associated with menarche before age 12. Conclusions: menarche is influenced by nutritional status and growth patterns in early childhood. For that reason, avoiding overweight and obesity in early childhood and keeping the normal pattern of growth- avoiding accelerated growth increments in early childhood- seems to be significant preventing health outcome in future life.